Overview of Compliance Implementation of Public and Community Health Protocol Implementation on Effort to Break the Chain of Transmission of the Covid-19 Virus - Firmansyah; Audila Sahira; Utia Rizka Hasanah; Arifah Farhah Nasution (International Archives of Medical Sciences and Public Health, 2021)
COVID-19 has been designated a global pandemic by the WHO because of the fast rate of spread between humans. WHO urges to practice physical distancing and implement health protocols as one of the initial preventive steps in breaking the chain of spread of COVID-19. Public places and facilities have a fairly large potential for COVID-19 transmission. For this reason, it is necessary to mitigate the impact of the COVID-19 pandemic to prevent the spread of COVID-19 in facilities or public places. This study aims to describe the implementation of health protocol compliance in the prevention and control of COVID-19 by providers of facilities or public places. This study is a study that uses a cross sectional design with a quantitative descriptive approach. Data collection is done through google form, then performed univariate data analysis. The results showed that as many as 471 (94.2%) public facilities implemented health protocols using masks, and 437 (87.4%) applied hand washing with running water. There are 447 (89.4%) public facilities that put up posters of the dangers of preventing COVID-19, and as many as 378 (75.6%) public facilities carry out cleaning with disinfectants. Based on the results of the study, it can be concluded that the application of the protocol health in public places during the COVID-19 pandemic is currently still relatively low. As a public place visited by many people, the public facility provider must implement health protocols in an effort to break the chain of transmission of the COVID-19 virus